2018
DOI: 10.1089/lap.2017.0692
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Assisted Transhiatal Esophagogastrectomy Without Thoracic or Cervical Access: A Series of One Hundred Three Consecutive Cases

Abstract: LTEG is a safe, feasible, and oncologically effective procedure for AEG when performed by an experienced surgeon. Laparoscopic surgery is associated with a lower risk of pleural rupture, but pleural rupture in laparoscopic surgery may cause an adverse effect on the recovery of pulmonary function presumably due to tension pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…After screening the title and abstract, 36 studies were assessed via full-text articles that we obtained. Finally, seven articles with a total of 1915 patients were included [13][14][15][16][17][18][19]. Approximately 1042 patients were in the LG group, while 873 patients were in the OG group.…”
Section: Selected Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening the title and abstract, 36 studies were assessed via full-text articles that we obtained. Finally, seven articles with a total of 1915 patients were included [13][14][15][16][17][18][19]. Approximately 1042 patients were in the LG group, while 873 patients were in the OG group.…”
Section: Selected Studiesmentioning
confidence: 99%
“…All selected studies reported the duration of surgery [13][14][15][16][17][18][19]. Four studies [15,16,18,19] showed that operative time was significantly longer in the LG group than in the OG group.…”
Section: Operative Timementioning
confidence: 99%
See 3 more Smart Citations